Wideband eight‐element antenna for 5G metal frame mobile phone applications. Issue 12 (30th September 2020) - Guo, Lin; Liu, Zheng; Liu, Heng; Huang, Daiwei; Du, Zhengwei
Abstract: A wideband eight‐element antenna based on slot modes for 5G metal frame mobile phones is proposed. The proposed antenna has two kinds of elements that both have four elements. Both kinds of elements consist of a coupled line and a closed slot. The slot sizes of the two kinds of elements are 26 mm × 2.5 mm and 28.5 mm × 2.5 mm, respectively. The measured working bands (under the condition of the reflection coefficients smaller than −6 dB) of the two kinds of elements are 3.3 to 5 GHz and 3.3 to 4.2 GHz, respectively. The eight elements can form an eight‐element MIMO antenna system working at the band of 3.3 to 4.2 GHz and a four‐element MIMO antenna system working at the band of 3.3 to 5 GHz. For the first kind of elements, the measured gains at the working band of 3.3 to 5 GHz are 2.23 to 4.29 dBi. For the second kind of elements, the measured gains at the working band of 3.3 to 4.2 GHz are 1.83 to 3.95 dBi. At the working bands, the measured isolations and efficiencies are bigger than 10 dB and 45%, respectively, the envelop correlation coefficients (ECCs) are smaller than 0.26, and the ratios of mean effective gains (MEGs) are smaller than 1.26 dB. With a 20 dB signal‐to‐noise ratio (SNR), at the band of 3.3 to 4.2 GHz, the ergodic channel capacity of the proposed eight‐element MIMO antenna system in an 8 × 8 MIMO system is 36.5 to 37.8 bps/Hz; at the band of 3.3 to 5 GHz, the ergodic channel capacity of the proposed four‐element MIMO antenna system in a 4 × 4 MIMO system is 18.5 to 19.6 bps/Hz.